Educational Video Quality on TikTok for Vocabulary Teaching - Bella Syifa Zulfia; Yokke Andini (LET: Linguistics, Literature and English Teaching Journal, 2023)
This research aimed to find out the quality of the educational videos and the quality of vocabulary teaching contents taught on the TikTok account. This research conducted online, on the TikTok account @jagobahasa.com. These data sources are limited to vocabulary teaching videos posted within the last three years. The researcher selected video samples randomly with the existing criteria. The criteria used to assess the quality were theories by Brame and Lopez. The study revealed that elements in the video showed a significant match against the criteria of educational video and criteria for vocabulary teaching contents. The educational videos provided cognitive load, student engagement and active learning. Meanwhile, the quality of the vocabulary teaching contents taught was nearly comprehensive, including teaching vocabulary of frequency, range, availability and expediency, learnability, and cultural factors. However, for the use of guiding questions, making videos as homework, and specific needs or interests of learners were not available.